The effect of spraying Gibberellin and sea algae extracts on characteristics of Vegetative growth, mineral contents and some characteristics of volatile oils in the fruit of Anise (Pimpinella anisum L.) - Mohammed Abdullah AL-Joburi (Tikrit Journal of Pure Science)
A field experiment was conducted in the nursery of the Tikrit University/Faculty of Agriculture, the agricultural season 2013- 2014 on Anise  plant. the Experiment design with randomized complete block design RCBD, the Experiment contained included two factors, the first one is Spraying Gibberellin GA3 with three levels (first, no Spraying labeled as A0 ,the second is Spraying with GA3 100 mg.L-1 labeled as A1, and the third is Spraying with GA3 200 mg.L-1 labeled as A2).The scend factor is Spraying with Sea Algae Extracts with four levels (the first is no Spraying level labeled as M0 ,the second is Spraying with Sea mino 1.5 ml.L-1 labeled as M1 the third is Spraying with Sea force 1 2.5 ml.L-1 labeled as M2, the fourth is Spraying with mixture of (Sea mino +Sea force 1 of concentration 1.5 ml. L-1 +2.5ml. L-1, labeled as M3) with three replications. the results showed the Spraying treatment of  GA3 200mg. L-1gave the height average in all the studied Characteristics of the vegetative growth. The Spraying treatment of Spraying with mixture Sea Algae Extracts (Sea mino +Sea force 1 of concentration 1.5ml. L-1 +2.5ml.L-1) gave the heiht average in all the studied Characteristics of the vegetative growth compared to the other treatments and the comparing treatment. For the overlapping treatment The Spraying treatment (A2M3) (Gibberellin 200 mg. L-1 + mixture of Sea mino + Sea force 1 of concentration 1.5 ml. L-1 +2.5 ml. L-1) in all of the Characteristics of the vegetative growth including the height of the plant (95.75) cm. plant -1, number of leaves (26.31) leaves. plant -1, dry weight for the vegetative sum (9. 41) gm. plant-1 , and the content of the total chlorophyll in the leaves (11.77) mg. gm-1.The comparing treatment gave the least of the above Characteristics (58.11 cm. plant -1, 11.06 leaves . plant -1, 4.15gm. plant -1 and 10.7 mg. gm-1) respectively. The treatment (A2M3) which is Spraying with (Gibberellin of concentration 200 mg. L-1) and Spraying with  mixture of Sea Algae Extracts (Sea mino + Sea force 1 of concentration 1.5 ml . L-1 +2.5ml. L-1) gave the hightest significant differences in the nutritious content of the leaves such nitrogen ,magnesium, iron, cuppar and zinc which are (2.513 %, 0.879 %, 80.27 mg. L-1, 14.34 mg. L-1 and 63.72 mg .L-1) respectively. The treatment (A2M1) which is Spraying with (gibberellin of concentration 200 mg. L-1) and spraying with (Sea mino of concentration 1.5ml. L-1) gave the hightest  concentration of phosphorus and putaseom  (0.393 % , and  2.873 %) respectively. For some  of the physical Characteristics of the Oil, The treatment (A2M3) and ( A2M1), gave the hightest significant  differences in terms of (Percentage, qualitative weight, Oil density, and reflection factor. The treatment (A2M3) gave the hightest concentration for the above Characteristics (2.49%, 0.961, 0.911 micro liter -1, 1.347degree)  respectively.